An evaluation study of service quality on tourist satisfaction at villas through digital communication - Budarsa, I Gde Ketut Sri; Sumadi, I Ketut; Sangka, I Nyoman Gde; Sajayasa, I Made; Sunaya, I Nengah; Widharma, I Gede Suputra; Abasana, I Gusti Ketut (Digital Theory, Culture & Society, 2025)
This study uses digital communication to evaluate service quality and its impact on tourist satisfaction at Villa Uluwatu. Combining qualitative and quantitative methods, data were gathered through interviews and observations, then analyzed using data adequacy, validity, and reliability tests, Service Quality analysis, and the Customer Satisfaction Index (CSI). Results show an 80% satisfaction rate, with weaknesses found in tangibles, reliability, responsiveness, assurance, and empathy. No attribute emerged as a strength. Key areas for improvement include parking facilities, employee appearance, service speed, housekeeping responsiveness, and administrative ease. The study recommends enhancing these aspects to boost tourist satisfaction and maintain market competitiveness.